The effects on the root and plant development of soybean of organic fertilizer applications (Bioscience Journal, 2022)
Organic fertilizers increase soil aeration, water and nutrient holding capacity, improve seed germination and encourage the production of thicker roots, increase the yield and quality of the crop. This study was aimed to determine the effects of organic fertilizer (vermicompost, sheep manure, cattle manure, poultry manure and inorganic fertilizer as control) applications on the root and plant development of soybean during two growth stages, namely third trifoliate stage (V3) and beginning of flowering of the plants (R1) in the pot condition. The experiment was established with a two-factorial randomized plot design with four replications. The fertilizer applications had a significant effect (p